Biocidal action, characterization, and molecular docking of Mentha piperita (Lamiaceae) leaves extract against Culex quinquefasciatus (Diptera: Culicidae) larvae. - Attiya Iqbal; Naveeda Akhtar Qureshi; Saleh S Alhewairini; Nargis Shaheen; Aneeqa Hamid; Muhammad Zahid Qureshi (PLoS ONE, 2022)
Mosquitoes are found in tropical and subtropical areas and are the carriers of a variety of diseases that are harmful to people's health. e.g., malaria, filariasis, chikungunya, dengue fever, etc. Although several insecticides are available, however, due to insect resistance and environmental hazards, more eco-friendly chemicals are needed for insect control. So, the current research was planned to explore the prospective of Mentha piperita to be used for the formulation of larvicides against mosquito Culex quinquefasciatus. The ethanolic and water extracts of M. piperita leaves were prepared using the soxhlet apparatus. The extracts were dried and subjected to prepare five concentrations multiple of 80 ppm. Each concentration was applied for its larvicidal efficacy setting an experiment (in triplicate) in plastic containers of 1000 ml with extracts, 30 larvae of all four instars separately, and fed with dog biscuits along with controls. Observations were taken after each 12 hrs. till 72 hrs. The antioxidant perspective of M. piperita was determined by DPPH radical scavenging, total antioxidant capacity, and ferric reducing power assays. Using brine shrimp lethality bioactivity, the cytotoxic study was perceived. Standard techniques were used to classify the M. piperita extract using preliminary qualitative and quantitative phytochemicals, UV-Vis spectroscopy, FT-IR, and GC-MS analysis. M. piperita ethanolic leaves extract after 24 hrs. of exposure in 400 ppm showed 93% (LC50 = 208.976 ppm) mortality in ethanolic extract and 80% (LC90 = 246.900 ppm) in the water extract. In treated larvae, biochemical examination revealed a substantial (P<0.05) decrease in proteins, carbohydrates, and fat contents. The ethanol extract of M. piperita was the most efficient, killing brine shrimp nauplii in 50% to 90% of cases. TAC (125.4 3.5gAAE/mg DW) and FRP (378.1 1.0gAAE/mg DW) were highest in the ethanolic extract of M. piperita. The presence of medicinally active components such as alkaloids, carbohydrates, flavonoids, and others in M. piperita leaves extract in ethanol was discovered. The UV-Vis spectrum showed two peaks at 209.509 and 282.814 nm with the absorption of 2.338 and 0.796 respectively. The FT-IR consequences exhibited the occurrence of alcohols, alkanes, aldehyde, aromatic rings, ether linkage, ester, and halo- compounds. The GC-MS analysis according to peak (%) area and retention time showed ten phytochemicals consisting of six major and four minor compounds. Among all the compounds, 1, 2-benzene dicarboxylic acid, and 3-ethyl-5, 5-dimethyl -6-phenyl bound well to the NS3 protease domain with PDB ID: 2FOM. Hence, for the prevention of health hazards and mosquito control, M. Piperita is a potential source of chemicals for insecticide formulation.